Performance of thermal-sprayed coatings to combat hot corrosion of coal-fired boiler tube and effect of process parameters and post-coating heat treatment on coating performance: a review - Kumar, Santosh; Handa, Amit; Chawla, Vikas; Grover, Neel Kanth; Kumar, Rakesh (Surface engineering, 2021)
High-temperature corrosion of coal-fired boiler parts such as water walls and superheated tubes poses a serious threat to the efficiency of the thermal power plant. To overcome this, numbers of corrosion control techniques are commonly employed. But, a dense and defect-free coating deposited by the thermal spray technique has shown promising result to combat hot corrosion. Although open or closed porosity in distinct thermal spray coatings can originate from distinct factors such as partial or totally un-molten particles, inadequate flow or fragmentation of the molten particle at impact, non-optimal spray angle and entrapped gas. But, this can still only be prevented by coating post-treatment. Hence, in this paper, authors have reviewed the performance of distinct coatings deposited by diverse thermal spray processes. Then, the effect of distinct process parameters and heat treatments on microstructure and mechanical properties of coatings is described. Finally, the best coatings are suggested to combat maximum hot corrosion of boiler tubes.